2016
DOI: 10.1007/s12010-016-2179-4
|View full text |Cite
|
Sign up to set email alerts
|

A Calcium-Ion-Stabilized Lipase from Pseudomonas stutzeri ZS04 and its Application in Resolution of Chiral Aryl Alcohols

Abstract: An extracellular organic solvent-tolerant lipase-producing bacterium was isolated from oil-contaminated soil samples and was identified taxonomically as Pseudomonas stutzeri, from which the lipase was purified and exhibited maximal activity at temperature of 50 °C and pH of 9.0. Meanwhile, the lipase was stable below or at 30 °C and over an alkaline pH range (7.5-11.0). Ca could significantly improve the lipase thermal stability which prompts a promising application in biocatalysis through convenient medium en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Especially Ca 2+ and Mg 2+ increased the activity of the recombinant LipB, reaching 201.53% and 182.47%, respectively, compared to the control. The results were consistent with previous studies that found Ca 2+ and Mg 2+ to be positive factors for lipases from Pseudomonas stutzeri ZS04 [44] and Serratia sp. W3 [45].…”
Section: Effects Of Metal Ions Compounds With Known Inhibitory Effect...supporting
confidence: 93%
See 1 more Smart Citation
“…Especially Ca 2+ and Mg 2+ increased the activity of the recombinant LipB, reaching 201.53% and 182.47%, respectively, compared to the control. The results were consistent with previous studies that found Ca 2+ and Mg 2+ to be positive factors for lipases from Pseudomonas stutzeri ZS04 [44] and Serratia sp. W3 [45].…”
Section: Effects Of Metal Ions Compounds With Known Inhibitory Effect...supporting
confidence: 93%
“…Former studies also reported similar results. For example, lipases from P. stutzeri ZS04 [44] and B. ubonensis SL-4 [7] were also stimulated by Tween-20 and Triton X-100. However, the activity of recombinant LipB was significantly decreased after treatment with EDTA, PMSF, DTT, and CTAB, and the effect became more obvious with the increase in concentration.…”
Section: Effects Of Metal Ions Compounds With Known Inhibitory Effect...mentioning
confidence: 99%
“…Under the same conditions, a lipase from Pseudomonas stutzeri retained 90% of activity. Unfortunately in this case performances in alcoholysis were not assessed [81]. Like many other lipases, the lipase from Proteus sp.…”
Section: Naturally Tolerant Lipasesmentioning
confidence: 99%
“…Microbial organisms serve as a huge repertoire for enzyme excavation and most industrially relevant enzymes are of microbial origin. Lipolytic enzymes are important biological compounds and become increasingly popular in the food, detergent, cosmetic, pharmaceutical, and pulp industries .…”
Section: Introductionmentioning
confidence: 99%